Impact of Nd Doping on Electronic, Optical, and Magnetic Properties of ZnO: A GGA + U Study - Qiao Wu; Gaihui Liu; Huihui Shi; Bohang Zhang; Jing Ning; Tingting Shao; Suqin Xue; Fuchun Zhang (Molecules, 2023)
The electronic, optical, and magnetic properties of Nd-doped ZnO systems were calculated using the DFT/GGA + U method. According to the results, the Nd dopant causes lattice parameter expansion, negative formation energy, and bandgap narrowing, resulting in the formation of an N-type degenerate semiconductor. Overlapping of the generated impurity and Fermi levels results in a significant trap effect that prevents electron-hole recombination. The absorption spectrum demonstrates a redshift in the visible region, and the intensity increased, leading to enhanced photocatalytic performance. The Nd-doped ZnO system displays ferromagnetic, with FM coupling due to strong spd-f hybridization through magnetic exchange interaction between the Nd-4f state and O-2p, Zn-4s, and Zn-3p states. These findings imply that Nd-doped ZnO may be a promising material for DMS spintronic devices.